Clinical outcome, risk assessment, and seasonal variation in hospitalized COVID-19 patients-Results from the CORONA Germany study. - Nele Gessler; Melanie A Gunawardene; Peter Wohlmuth; Dirk Arnold; Juergen Behr; Christian Gloeckner; Klaus Herrlinger; Thomas Hoelting; Ulrich-Frank Pape; Ruediger Schreiber; Axel Stang; Claas Wesseler; et al. (PLoS ONE, 2021)
Background After one year of the pandemic and hints of seasonal patterns, temporal variations of in-hospital mortality in COVID-19 are widely unknown. Additionally, heterogeneous data regarding clinical indicators predicting disease severity has been published. However, there is a need for a risk stratification model integrating the effects on disease severity and mortality to support clinical decision-making. Methods We conducted a multicenter, observational, prospective, epidemiological cohort study at 45 hospitals in Germany. Until 1 January 2021, all hospitalized SARS CoV-2 positive patients were included. A comprehensive data set was collected in a cohort of seven hospitals. The primary objective was disease severity and prediction of mild, severe, and fatal cases. Ancillary analyses included a temporal analysis of all hospitalized COVID-19 patients for the entire year 2020. Findings A total of 4704 COVID-19 patients were hospitalized with a mortality rate of 19% (890/4704). Rates of mortality, need for ventilation, pneumonia, and respiratory insufficiency showed temporal variations, whereas age had a strong influence on the course of mortality. In cohort conducting analyses, prognostic factors for fatal/severe disease were: age (odds ratio (OR) 1.704, CI:[1.221-2.377]), respiratory rate (OR 1.688, CI:[1.222-2.333]), lactate dehydrogenase (LDH) (OR 1.312, CI:[1.015-1.695]), C-reactive protein (CRP) (OR 2.132, CI:[1.533-2.965]), and creatinine values (OR 2.573, CI:[1.593-4.154]. Conclusions Age, respiratory rate, LDH, CRP, and creatinine at baseline are associated with all cause death, and need for ventilation/ICU treatment in a nationwide series of COVID 19 hospitalized patients. Especially age plays an important prognostic role. In-hospital mortality showed temporal variation during the year 2020, influenced by age. Trial registration number NCT04659187.